The kiss-1-kisspeptin-gpr54 complex, a critical modulator of GnRH neurons during pubertal activation - Meza-Herrera, César Alberto; Veliz-Deras, Francisco Gerardo; Wurzinger, Maria; López-Ariza, Bernardo; Arellano-Rodriguez, Gerardo; Rodriguez-Martinez, Rafael (Journal of Applied Biomedicine, 2010)
Establishment of the hypothalamic-hypophyseal-gonadal function is dependent on the highly controlled and dynamic interactions between regulatory signals from the brain, pituitary and gonads, all of them leading to the attainment of reproductive capacity, where a coordinated and timely activation of GnRH neurons must occur. The GnRH neurons extend their neurosecretory axons to the hypothalamus where GnRH is released into the pituitary portal vessels to elicit the secretion of LH and FSH, which in turn, will promote gonadal development and support reproductive physiology. Genetic studies have demonstrated that disabling mutations and targeted deletions of the G-protein-coupled receptor (GPR54) generated hypogonadotropic hypogonadism. This link between GPR54 and reproduction, generated attention to the natural ligands of the GPR54 receptor, known as kisspeptins, which are translational products of the hypothalamic gene KiSS1. Recent advances in kisspeptin research have defined a major role of this molecule in controlling the onset of the reproductive function observed at puberty. The aim of this review is to highlight the basic endocrine and genetic concepts involved in the establishment of the hypothalamic-hypophyseal-gonadal axis function which promotes the onset of the reproductive function during puberty. The review highlights what is currently known about the kisspeptin-GPR54 signalling system in the activation of the GnRH neurons.
Keywords: systém hypofýza - nadledviny; financování organizované; hormon uvolňující gonadotropiny; Receptors, G-Protein-Coupled; systém hypotalamus-hypofýza; Financing, Organized; receptory spřažené s G-proteiny; Pituitary-Adrenal System; Gonadotropin-Releasing Hormone; lidé; Neurons; reprodukční systém - fyziologické jevy; Hypothalamo-Hypophyseal System; puberta; Puberty; neurony; Reproductive Physiological Phenomena; Humans